Goldkrug, Post Kokoschken Bes. Albert Tarnowski. Telefon 4. - Paul Lukowski (Gdańsk). (Danzig-Langfuhr : Paul Lukowski, Postkartenverlag, 1914)
Przedstawia ogród restauracji Alberta Tarnowskiego w Złotej Karczmie, ok. 1915 r.
Data wg biogramu wyd.